Utilizing Smart Ladder Media to Enhance Student Learning Outcomes on Length Units in Third-Grade Elementary School - Ripo, Helena Enselmini; Ndori, Vinsensius Herianto; Dhema, Magdalena (The Indonesian Institute of Science and Technology Research, 2024)
This study aims to assess the mathematics learning outcomes of third-grade students at MIS Muhammadiyah Darussalam Waioti, Sikka (a private elementary school) on the topic of length units using the